Problem of doping in sport among students of secondary schools and sport oriented educational institutions - A. A. Derevoedov; M. S. Sherbal; A. V. Rogatyuk; I. V. Zagorskiy; A. V. Zorenko (National Electronic Information Consortium (NEICON), 2020)
Objective: to study the attitude towards doping among students in Russian sport. Materials and methods: sociological quantitative on-line research using river-sampling was conducted among students of secondary and high school education engaged in physical culture on a regular basis and also among students choosing a specialization in the sphere of physical culture and sport including supplementary education programs of secondary specialized education. Study included 450 secondary school students (Group#l) and 450 secondary specialized education students in the sphere of physical culture and sport (Group#2). Results: the research carried out that the students' attitude towards doping was similar. Negative assessment of misuse of prohibited substances was consistent alongside with support of anti-doping educational programs and activities. Low level of awareness about the issue of doping in sport was detected. Conclusions: creating and implementing robust anti-doping educational program aimed at different target audiences (taking into account sport specific and awareness level) are the main ways to the effective fight against doping in sport.